Strengthening Anti-Money-Laundering (AML) Systems through Information Systems Auditing: Evaluating Data Integrity, Transaction Reporting, and System Controls (gjstudies, 2024)
This research examines how Information Systems auditing strengthens AntiMoney-Laundering (AML) systems through comprehensive evaluation of data integrity, transaction reporting mechanisms, and system controls in financial institutions. Through empirical analysis of 189 financial institutions across multiplejurisdictions from 2021 to 2024, this study develops a systematic framework for assessing AML system effectiveness through specialized IS audit methodologies. Theresearch introduces a novel AML System Integrity Score (ASIS) that quantifiescontrol effectiveness across data quality, transaction monitoring, and regulatory reporting dimensions. Empirical results demonstrate that institutions implementingcomprehensive IS audit programs for AML systems achieve 67% higher detectionrates for suspicious activities and 54% improvement in regulatory reporting accuracy compared to those with limited audit coverage. The study reveals that dataintegrity issues account for 42% of AML system failures, while inadequate transaction monitoring controls represent the most significant compliance risk. Findingsindicate that effective AML system auditing requires specialized technical expertise,advanced data analytics capabilities, and systematic control evaluation methodologies. This research contributes both theoretical advancements in AML complianceassurance and practical implementation guidelines for financial institutions seeking to enhance their anti-financial crime capabilities through robust informationsystems auditing.